2017
DOI: 10.3389/fmicb.2017.01218
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of 2,4-Diacetylphloroglucinol Biosynthetic Genes among the Pseudomonas spp. Reveals Unexpected Polyphyletism

Abstract: Fluorescent pseudomonads protecting plant roots from phytopathogens by producing 2,4-diacetylphloroglucinol (DAPG) are considered to form a monophyletic lineage comprised of DAPG+ Pseudomonas strains in the “P. corrugata” and “P. protegens” subgroups of the “Pseudomonas fluorescens” group. However, DAPG production ability has not been investigated for many species of these two subgroups, and whether or not the DAPG+ Pseudomonas are truly monophyletic remained to be verified. Thus, the distribution of the DAPG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 58 publications
(84 reference statements)
3
62
1
2
Order By: Relevance
“…Some Pseudomonas species, such as P. fluorescens, P. protegens, P. kilonensis, P. chlororaphis, and P. simiae, have been used widely in agriculture to control plant disease and to improve production (Raaijmakers, Weller, & Thomashow, 1997;Ramamoorthy, Raguchander, & Samiyappan, 2002). Among them, P. kilonensis F113, P. protegens strains CHA0 and Pf-5, and some other typical PGPR strains produced polyketides, such as 2,4-diacetylphloroglucinol (DAPG), phenazines, pyoluteorin, and pyrrolnitrin, that defended against a broad range of plant pathogens (Almario et al, 2017;Iavicoli, Boutet, Buchala, & Métraux, 2003;Keel et al, 1992;Nowak-Thompson, Gould, & Loper, 1997;Ramette et al, 2011). In addition to polyketides, many PGPR strains synthesized cyclic lipopeptides (CLPs) by non-ribosomal peptide synthetases (NRPSs) as potent secondary metabolites that can destroy microbial membranes (Geudens & Martins, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some Pseudomonas species, such as P. fluorescens, P. protegens, P. kilonensis, P. chlororaphis, and P. simiae, have been used widely in agriculture to control plant disease and to improve production (Raaijmakers, Weller, & Thomashow, 1997;Ramamoorthy, Raguchander, & Samiyappan, 2002). Among them, P. kilonensis F113, P. protegens strains CHA0 and Pf-5, and some other typical PGPR strains produced polyketides, such as 2,4-diacetylphloroglucinol (DAPG), phenazines, pyoluteorin, and pyrrolnitrin, that defended against a broad range of plant pathogens (Almario et al, 2017;Iavicoli, Boutet, Buchala, & Métraux, 2003;Keel et al, 1992;Nowak-Thompson, Gould, & Loper, 1997;Ramette et al, 2011). In addition to polyketides, many PGPR strains synthesized cyclic lipopeptides (CLPs) by non-ribosomal peptide synthetases (NRPSs) as potent secondary metabolites that can destroy microbial membranes (Geudens & Martins, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The polyketide antibiotic DAPG, which targets key physiological processes involving membrane function, reactive oxygen regulation, and cellular homeostasis, is active against a wide variety of organisms including viruses, bacteria, fungi, oomycetes, parasitic worms, and even plants including different cultivars of wheat . DAPG producers have been recovered from plant rhizospheres worldwide, with the biosynthesis genes broadly conserved and embedded within the genomes of members of at least five species ( P. protegens, P. brassicacearum, P. kilonensis, P. thivervalensis, and P. gingeri ) within the P. corrugata and P. protegens subgroups of P. fluorescens , as well as a few β‐proteobacteria ( Chromobacterium vaccinii , C. piscinae , and Pseudogulbenkiania ferrooxidans ) . The antibiotic is a strong inducer of systemic resistance (ISR) in Arabidopsis , a form of plant immunity defined as the ‘enhanced defensive capacity of the entire plant against a broad spectrum of pathogens; acquired upon local induction, for example, at roots, by beneficial microbes” .…”
Section: Model Systems In Pseudomonasmentioning
confidence: 99%
“…17 DAPG producers have been recovered from plant rhizospheres worldwide, with the biosynthesis genes broadly conserved and embedded within the genomes of members of at least five species (P. protegens, P. brassicacearum, P. kilonensis, P. thivervalensis, and P. gingeri) within the P. corrugata and P. protegens subgroups of P. fluorescens, as well as a few -proteobacteria (Chromobacterium vaccinii, C. piscinae, and Pseudogulbenkiania ferrooxidans). 18 The antibiotic is a strong inducer of systemic resistance (ISR) in Arabidopsis, a form of plant immunity defined as the 'enhanced defensive capacity of the entire plant against a broad spectrum of pathogens; acquired upon local induction, for example, at roots, by beneficial microbes". 19 It is important to note that not all members of the microbiome are capable of inducing ISR, that other bacterial inducers may function in different plant hosts, and that the phenomenon ultimately depends on production of chemical signals that mediate communication between the inducing organism and the host plant, a hallmark of the level of interaction within the holobiont.…”
Section: 4-diacetylphloroglucinol (Dapg) and Suppressive Soilsmentioning
confidence: 99%
“…[8] The acylations are mostly performed in organic solvents (e. g., nitrobenzene or nitromethane) or at elevated temperatures of up to 300°C. [10] Subsequently, it was shown that a homologue acyltransferase from Pseudomonas protegens (PpATaseCH) exhibits promiscuous activity, accepting also non-natural, activated esters, like isopropenyl acetate, phenyl acetate and N-acetyl imidazole for the biocatalytic Friedel-Crafts acylation of resorcinol derivatives leading to C4-acylated products. As an alternative, a biocatalytic approach running the reaction in aqueous media was recently published: originally an acyltransferase from Pseudomonas fluorescens was found to be involved in CÀ C bond formation in the biosynthesis of 2,4-diacetylphloroglucinol (DAPG).…”
Section: Introductionmentioning
confidence: 99%